Practical Considerations of Mapping Persistent Atrial Fibrillation With Whole-Chamber Basket Catheters - Laughner, Jacob; Shome, Shibaji; Child, Nicholas; Shuros, Allan; Neuzil, Petr; Gill, Jaswinder; Wright, Matthew (JACC. Clinical electrophysiology, 2016)
OBJECTIVES: This study sought to evaluate basket catheter deployment, catheter-tissue contact, and time-space stability of unipolar atrial electrograms (aEGMs) recorded in persistent atrial fibrillation (AF) patients. BACKGROUND: Panoramic mapping of human AF using multiple-electrode basket catheters may identify AF sources. Although clinical results using this technique are provocative, questions remain about its effectiveness. METHODS: Data were collected from patients (N = 25) undergoing catheter ablation for AF during the multicenter STARLIGHT (Signal Transfer of Atrial Fibrillation Data to Guide Human Treatment) trial (NCT01765075). Left and right aEGM signals were recorded using basket catheters during baseline AF, following ablation and during sinus rhythm. Data were analyzed for basket deployment, peak-to-peak voltage, and electrogram stability and organization. Electrogram stability and organization were evaluated via time-frequency analysis (TFA). RESULTS: Basket catheters displayed equatorial bunching when deployed in atria. Interspline spacing ranged from 1.7 to 64.0 mm in the right atrial and from 1.5 to 85.08 mm in the left atrial basket. Approximately one-third of mapping electrodes failed to demonstrate a median peak-to-peak voltage >2× the low-voltage threshold. Time-space stability and organization was observed in 13 of 22 (59.09%) right atrial and 10 of 22 (45.45%) left atrial baskets. CONCLUSIONS: Despite poor deployment and a large number of low-voltage electrodes, stability and organization was observed in about one-half of the mapped patients. Although this study suggests that basket catheters have limitations for patient-specific AF mapping, concordant activation occurs in some persistent AF patients, which may be amenable to high-density mapping techniques.
Keywords: rotors; stability; organization; basket mapping; atrial fibrillation